Reduced Ceftazidime-Avibactam Susceptibility in KPC-Producing Klebsiella pneumoniae From Patients Without Ceftazidime-Avibactam Use History – A Multicenter Study in China - Cui, Xiaoyan; Shan, Bin; Zhang, Xue; Qu, Fen; Jia, Wei; Huang, Bin; Yu, Hua; Tang, Yi-Wei; Chen, Liang; Du, Hong (Frontiers in Microbiology, 2020)
KPC-producing Klebsiella pneumoniae (KPC-KP) is the most widely spread carbapenem-resistant Enterobacteriaceae (CRE) in China. Avibactam is a novel β-lactamase inhibitor which is highly active against KPC. Recently, ceftazidime-avibactam (CAZ-AVI) was approved for clinical treatment in China. Here we conducted a retrospective study to examine the antimicrobial susceptibility of CAZ-AVI prior to its usage in China, and evaluated the potential to develop resistance in KPC-KP. CAZ-AVI MICs were tested in 361 KPC-KP isolates collected from six medical centers in China. Twelve (3.3%) isolates showed reduced susceptibility (MIC ≥4/4 μg/ml). These isolates are multidrug-resistant and half of them carry virulence genes. All of these isolates belong to ST11. In comparison to susceptible strains, these isolates demonstrated higher blaKPC-2 copy numbers and expressions. And in in vitro selection testing, these isolates performed higher frequency of developing CAZ-AVI resistance. Taken together, our study demonstrated that CAZ-AVI has potent in vitro activities against KPC-KP in China, and highlighted the clinical significance of KPC-KP with reduced susceptibility to CAZ-AVI isolated from patients with no prior treatment with this combination.